Induction of Protective Immunity against Toxoplasma gondii in Mice by Nucleoside Triphosphate Hydrolase-II (NTPase-II) Self-amplifying RNA Vaccine Encapsulated in Lipid Nanoparticle (LNP) - Luo, Fangjun; Zheng, Lina; Hu, Yue; Liu, Shuxian; Wang, Yan; Xiong, Zhongkui; Hu, Xin; Tan, Feng (Frontiers in Microbiology, 2017)
RNA-based vaccine represents an irresistible and safe immunization strategy with decreasing theoretical risks of genomic integration and malignant cell transformation. To our knowledge, however, there is no report about development of RNA vaccine against T. gondii infection. We have previously demonstrated that the recombinant Toxoplasma gondii nucleoside triphosphate hydrolase-II (NTPase-II) protein is able to provide protective Th1 cell-mediated immunity against T. gondii. Herein, we evaluated the immunogenic potential of a self-amplifying RNA vaccine encoding T. gondii NTPase-II gene, RREP-NTPase-II, delivered by a synthetic lipid nanoparticle (LNP). Immunization of mice with naked RREP-NTPase-II induced a strong cellular and humoral immune response with high IgG antibody titers and IFN-γ production. The immunized mice displayed significantly prolonged survival time and reduction in brain parasite load (46.4%) compared with control group. Furthermore, mice vaccinated with RREP-NTPase-II encapsulated LNP displayed significantly enhanced protection against acute infection as well as chronic infection with PRU cyst, which shows 62.1% reduction in brain cyst burden in comparison to control group. These results suggest that the combination of self-amplifying RNA and LNP ion would be beneficial to the development of a safe and long-acting vaccine against toxoplasmosis.